On the influence of elastic interphase deformations on the width of reflections from the released phase in dispersion hard-ening alloys - A. V. Tolstoy (Литьë и металлургия)
The influence of fields of elastic interphase deformations on the amount of broadening of reflections from the separation phase is studied. It is established that elastic interphase deformations in strongly distorted crystals have a significant effect on the amount of broadening of reflections from the separation phase. Due to the fact that the broadening of the diffraction lines is used to judge the size of the selection particles, this leads to a significant error in estimating their true value. Therefore, the influence of elastic interphase strain fields should certainly be taken into account when determining particle sizes from x-ray data.